Effects of gut microbiota on neurodegenerative diseases - Khatoon, Saima; Kalam, Nida; Rashid, Summya; Bano, Gulnaz (Frontiers in Aging Neuroscience, 2023)
A progressive degradation of the brain's structure and function, which results in a reduction in cognitive and motor skills, characterizes neurodegenerative diseases (NDs) such Alzheimer's disease (AD), Parkinson's disease (PD), Amyotrophic lateral sclerosis (ALS) and Huntington's disease (HD). The morbidity linked to NDs is growing, which poses a serious threat to human beings' ability to live well, mentally and physically. The gut-brain axis (GBA) is now known to have a crucial role in the emergence of NDs. The gut microbiota serves as a conduit for the GBA, a two-way communication system between the gut and the brain. The myriad of microorganisms that make up the gut microbiota can affect brain physiology by transmitting numerous microbial chemicals from the gut to the brain via the GBA or neurological system. The synthesis of neurotransmitters, the immunological response, and the metabolism of lipids and glucose have all been demonstrated to be impacted by alterations in the gut microbiota, such as an imbalance of helpful and harmful bacteria. For the purpose of creating innovative interventions and clinical therapies for NDs, it is crucial to comprehend the participation of the gut microbiome in these conditions. In addition to using antibiotics and other drugs to target particular bacterial species that may be a factor in NDs, this also includes the use of probiotics, and other faecal microbiota transplantation to maintain a healthy gut microbiome. In conclusion, the examination of the GBA can aid in understanding the etiology and development of NDs, which may benefit in the improvement of clinical treatments for these disorders as well as ND interventions. This study provides an indication of existing knowledge about the involvement of microbiota present in gut in NDs and potential treatment options. Keywords: Neurodegenerative diseases, gut-brain axis, microbiome, Alzheimer’s disease, Parkinson’s disease, Huntington’s disease